Effect of platelet storage duration on clinical outcomes and incremental platelet change in critically ill children. Issue 12 (22nd September 2020) - Nellis, Marianne E.; Spinella, Philip C.; Tucci, Marisa; Stanworth, Simon J.; Steiner, Marie E.; Cushing, Melissa M.; Davis, Peter J.; Karam, Oliver; ,
Background: The safety of platelet (PLT) concentrates with longer storage duration has been questioned due to biochemical and functional changes that occur during blood collection and storage. Some studies have suggested that transfusion efficacy is decreased and immune system dysfunction is worsened with increased storage age. We sought to describe the effect of PLT storage age on laboratory and clinical outcomes in critically ill children receiving PLT transfusions. Study Design and Methods: We performed a secondary analysis of a prospective, observational point‐prevalence study. Children (3 days to 16 years of age) from 82 pediatric intensive care units in 16 countries were enrolled if they received a PLT transfusion during one of the predefined screening weeks. Outcomes (including PLT count increments, organ dysfunction, and transfusion reactions) were evaluated by PLT storage age. Results: Data from 497 patients were analyzed. The age of the PLT transfusions ranged from 1 to 7 days but the majority were 4 (24%) or 5 (36%) days of age. Nearly two‐thirds of PLT concentrates were transfused to prevent bleeding. The indication for transfusion did not differ between storage age groups ( P = .610). After patient and product variables were adjusted for, there was no association between storage age and incremental change in total PLT count or organ dysfunction scoring. A significant association between fresher storage age and febrile transfusion reactions ( P = .002) was observed. Conclusion: The results in a large, diverse cohort of critically ill children raise questions about the impact of storage age on transfusion and clinical outcomes which require further prospective evaluation.